PERKEMBANGAN.FRINGE-SETTLEMENTS.DI iKAWASAN.RURAL-URBAN.FRINGE. - Elias, Stefharen Elshaday; Rondonuwu, Dwight M; Tondobala, Linda (SPASIAL, 2021)
Talawaan District. Kalawat, and Tombulu are sub-districts located on the outskirts of Manado City which are affected by Manado City, one of which is the increase in housing and settlements. In the Regional Spatial Plan of the three sub-districts, development is directed into new settlements that are able to accommodate the shortage of houses in Manado City. This study aims to identify the physical conditions in the rural urban fringe area and analyze the development pattern of fringe settlements in the rural urban fringe area. The survey method used in this research is descriptive and qualitative which is supported by quantitative analysis to analyze the data in digital form and can also be measured based on the standard used and also using spatial analysis spatial analysis by using descriptive qualitative method and a map of the use of land for settlements, with the aim of describing the development and expansion that has occurred, which is then analyzed for the pattern of distribution of settlements that occurs using the closest-neighborhood analysis. The results of the analysis are expected to be a reference for the government to treat development restrictions and supervision so as not to interfere with spatial patterns and spatial structures in the three sub-districts in the next few years.Keywords: Rural Urban Fringe, Fringe Settlements